Design and Implementation Multimedia Learning Success for Vocational Schools - Fitro Nur Hakim; Achmad Solechan (Institute of Advanced Engineering and Science, 2018)
This research aims to design a web-based multimedia applications, interactive learning, in order to improve the learning outcomes of students, especially students of Vocational High School. Multimedia Learning has been designed with some additional content in the form of applications: decision support system for multimedia usage based on Model of Multimedia Learning Success. The population obtained from respondents vocational school in Central Java, which is already implementing multimedia learning. The method used is qualitative analysis in the form of: the development of multimedia learning integrated with decision support systems. Design and implementation of multimedia learning success system that is abbreviated